2019
DOI: 10.1182/blood.2019000069
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of nilotinib in pediatric patients with Philadelphia chromosome–positive chronic myeloid leukemia

Abstract: Key Points Nilotinib demonstrated efficacy and a manageable safety profile in pediatric patients with newly diagnosed and pretreated Ph+ CML-CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 29 publications
6
64
0
Order By: Relevance
“…However, there was no increased rate of grade 3 AEs in patients treated with multiagent chemotherapy. Overall, rates of serious AEs were lower in this study than reported in adults, which is consistent with studies of second‐generation TKIs in paediatrics (Hijiya et al , ; Gore et al , ).…”
Section: Patient and Disease Characteristics Treatment Details Toxisupporting
confidence: 91%
“…However, there was no increased rate of grade 3 AEs in patients treated with multiagent chemotherapy. Overall, rates of serious AEs were lower in this study than reported in adults, which is consistent with studies of second‐generation TKIs in paediatrics (Hijiya et al , ; Gore et al , ).…”
Section: Patient and Disease Characteristics Treatment Details Toxisupporting
confidence: 91%
“…[14][15][16] The second-generation TKIs (2G-TKIs) dasatinib and nilotinib were approved recently as first-line treatment in children, which has expanded treatment options and made allogeneic stem cell transplantation (allo-SCT) a third-line treatment. 17,18 However, because children are actively growing during TKI treatment, they face unique side effects not seen in adults, such as growth disturbance. [19][20][21][22][23] Discontinuing TKIs in patients with a deep and sustained molecular response is feasible in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] More recently, initial pediatric data are now available for second-generation tyrosine kinase inhibitors (TKIs), including dasatinib and nilotinib. 8,9 TKI monotherapy is considered standard therapy for those presenting in CP with adequate disease response. HSCT is now considered only in a subset of children with CML, namely those who present with, or progress to, blast phase.…”
mentioning
confidence: 99%